Pengaruh Promosi Kesehatan tentang Kesehatan Reproduksi terhadap Pengetahuan dan Sikap Remaja tentang Seks Pranikah di SMA Muhammadiyah 4 Surakarta - Saputro, Dodi Nur Afif Ageng; , Arif Widodo, A.Kep., M.kes; , Endang Zulaicha S, S.Kp., M.Kep (2015)
The incident cases pregnant of adolescent before marriage, is an example of understand to knowledge, attitude and behavior still lack of reproduction health. One of effort to improve knowledge of adolescents about reproduction health is giving promoting health. The objective is to influence of health promotion of reproduction health to knowledge and attitudes andolescent of sex premarriage at Muhammadiyah 4 High School of Kartasura. The study use a method of quasi experiment, design with pre and post test with control group. Sample are 40 students from x and xi classes, and divided into 20 students for case group, and 20 students for control group. Data analysis use paired sample test and independent sample test. results of study that there is a differences of knowledge student about reproductive health before and after given health promotion with p= 0,001 in treatment group, meanwhile in control group there is no differences with p= 0,437. There is differences attitude student about reproductive health before and after given health promotion for with p= 0,002 of treatment group, meanwhile in control group there is no differences with p = 0,746. There is different influence health promotion to knowledge about reproductive health between case group with control group with p = 0,001.There is no influence of health promotion for attitude student of reproductive health between case group and control group with p = 0,092. The research conclusion there is influence health education toward increasere respondent knowledge about reproduction health, however there is no dinfluence helath education toward increase attitude.